Multi-scale mechanisms of twinning-detwinning in magnesium alloy AZ31B simulated by crystal plasticity modeling and validated via in situ synchrotron XRD and in situ SEM-EBSD - Zhang, H; Jerusalem, A; Salvati, E; Papadaki, C; Fong, K; Song, X; Korsunsky, A (Elsevier, 2019)
We present a combined experimental and numerical study that provides the understanding of deformation mechanisms and stresses in Mg AZ31B alloy across scales, from macro-scale (Type I) to micro- (inter-granular, Type II) and nano-scale (intra-granular, Type III). The combination of in situ synchrotron X-ray diffraction (XRD), in situ electron backscattered diffraction (EBSD) and crystal plasticity finite element (CPFE) modeling of crystal slip and twinning/detwinning was employed. The crystal rotation observed directly in the XRD and EBSD experiments revealed the onset and completion of the twinning/detwinning processes during in situ cyclic compression-tension loading. It also allowed reliable calibration of the key model parameters, in particular critical resolved shear stress (CRSS) of detwinning. The validation of the model was performed at distinct different scales corresponding to all stress types. Direct comparison with the data from the loading device provided the confirmation of the model validity in terms of correct description of the macroscopic stress-strain response (Type I stresses). The calibration led to the CRSS detwinning value of 23 MPa, and twinning of 46.5 MPa. At the inter-granular micro-scale (Type II stresses), the model satisfactorily predicted the transition between different plastic deformation modes (slip, twinning and detwinning), as confirmed by the comparison with peak intensities in XRD experiments. For the intra-granular (nano-scale) Type III stresses, it was concluded that the model was also valid at the level of statistical description (rather than local behavior). Namely, it has not been possible to predict correctly the real morphology of the twins observed in EBSD experiments.